Performance of Johor port after the second phase expansion programme / Ahmad Fauzi Ali - Ali, Ahmad Fauzi (1990)
The study on performance of Johor Port after the second phase expansion programme involves recording of data and a series of analysis on the performance of the port especially with the new facilities after the second phase expansion programme. It also involves the study on the effort made by Johor Port to market its port facilities and to attract more traders and shipping lines. This includes Johor Port's marketing strategy, Free Trade Zone (FTZ) to make Johor Port become more attractive and competitive as Port of Singapore, and proposal of privatising the port to improve productivity and efficiency. Finally, it study on the impact of the second phase expansion programme to the cargo trend in Johor Port especially in term of containerisation. It also study on the containerise cargoes that go through the causeway, the reasons and whether these? Cargoes could be diverted to Johor Port or not.